Hungarian Monitoring, 17 August 1989 . [Magyar rádiófigyelő], 1989. augusztus 17 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Moscow acknowledges approval of Polish and Hungarian reforms as long as they do not provoke foreign affairs - Polish Senate's unequivocal criticism of 1968 intervention in Czechoslovakia - Czechoslovak government states it will impede opposition movements - Efforts to form government in Poland Domestic Affairs: - Government in session: roundtable talks; modifying criminal law code; emigration and immigration and bill concerning passports. - Laws forbidding religious orders from operating to be abolished, college for the disabled - Lajos Czinege on the 1968 intervention - National demonstration against price increases in meat products - Opposition Roundtable criticizes Demisz petition and Géza Kilényi Economy: - Hungarian-Hong Kong economic relations - Car trade should be liberalized, says deputy finance minister Járai Külpolitika: - Moszkva jóváhagyólag tudomásul veszi a lengyel és magyar reformokat, ha nem érik külpolitikai provokációk - A lengyel szenátus egyértelműen elítélte az 1968-as csehszlovákiai beavatkozást - A CS kormány nyilatkozata, hogy megakadályozza az ellenzék megmozdulásait - Kormányalakítási erőfeszítések Lengyelországban Belpolitika: - Kormányülés: kerekasztal-tárgyalások; Btk. módosítás; a ki - És bevándorlásról, valamint az útlevélről szóló törvényjavaslat. - Megszűnnek a szerzetes rendek működését tiltó jogszabályok, főiskolát kapnak a mozgássérültek - Czinege Lajos a 68-as bevonulásról - Országos tiltakozó akció a húskészítmények áremelése miatt - Az Ellenzéki Kerekasztal bírálja a DEMISZ-t az aláírásgyűjtési akció miatt, valamint Kilényi Gézát Gazdaság: - Magyar-hongkongi gazdasági kapcsolatok - Szabaduljon fel az autókereskedelem, mondja Járai pénzügyminiszter helyettes